2016
DOI: 10.3126/jnps.v36i1.14386
|View full text |Cite
|
Sign up to set email alerts
|

Knowledge, Attitude and Socio-cultural Beliefs of Adolescent Girls towards Menstruation

Abstract: Introduction: Knowledge regarding physiology of menstruation and hygienic practices are poor in adolescent girls. Deep rooted social beliefs make their attitude more negative.Material and Methods: In a hospital based cross sectional study, one hundred adolescent girls who have attained menarche were interviewed with a pre-validated semi-structured questionnaire to assess their knowledge, experiences, effect of mother’s education on menstrual hygienic practices and factors affecting their positive and negative … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
4
0
1

Year Published

2018
2018
2021
2021

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 6 publications
1
4
0
1
Order By: Relevance
“…Similar result were found in another study where the mean age at menarche was found to be 13.1 year [3] and13.28 years [12]. In a study from Saudi Arebia, the mean menarcheal age was quite low (12.08 year) [13].…”
Section: Discussionsupporting
confidence: 86%
See 3 more Smart Citations
“…Similar result were found in another study where the mean age at menarche was found to be 13.1 year [3] and13.28 years [12]. In a study from Saudi Arebia, the mean menarcheal age was quite low (12.08 year) [13].…”
Section: Discussionsupporting
confidence: 86%
“…Inanother study it was found that 75% wrap in paper/polythene bag and dispose [12]. In this study, 60.6% used to clean genitalia during menstruation with soap-water where as in another study 66.54% girls were using water to clean genitals during menstruation [15].…”
Section: Discussionmentioning
confidence: 53%
See 2 more Smart Citations
“…The results of other studies also mentioned that 99 out of 100 respondents said that they were worried about menstruation. As many as 71% of girls lack of knowledge and they were not psychologically prepared about menstruation and 72% was lack of information about how to use pads before menarche (Kapoor & Khari, 2016).…”
Section: Knowledgementioning
confidence: 99%